2007
DOI: 10.1086/523257
|View full text |Cite
|
Sign up to set email alerts
|

The Luminosity Function of Low‐Redshift Abell Galaxy Clusters

Abstract: We present the results from a survey of 57 low-redshift Abell galaxy clusters to study the radial dependence of the luminosity function (LF). The dynamical radius of each cluster, r 200 , was estimated from the photometric measurement of cluster richness, B gc . The shape of the LFs is found to correlate with radius such that the faint-end slope, , is generally steeper on the cluster outskirts. The sum of two Schechter functions provides a more adequate fit to the composite LFs than a single Schechter function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
128
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(150 citation statements)
references
References 80 publications
(214 reference statements)
19
128
3
Order By: Relevance
“…Our best fit parameters are: N = 260 ± 45 gal/mag/deg 2 , M = −21.8 ± 0.2 and α = −0.8 ± 0.1, with a reduced χ 2 = 0.57. The value of M is rather close to the value found by Barkhouse et al (2007) (M * = −22.36, obtained with a fixed the faint end slope α = −1) and is typical for rich clusters. The faint end slope is found slightly larger than the canonical value α = −1 but it has a large uncertainty associated to the background corrections in our sample S3.…”
Section: The Luminosity Function Of a 1413supporting
confidence: 88%
“…Our best fit parameters are: N = 260 ± 45 gal/mag/deg 2 , M = −21.8 ± 0.2 and α = −0.8 ± 0.1, with a reduced χ 2 = 0.57. The value of M is rather close to the value found by Barkhouse et al (2007) (M * = −22.36, obtained with a fixed the faint end slope α = −1) and is typical for rich clusters. The faint end slope is found slightly larger than the canonical value α = −1 but it has a large uncertainty associated to the background corrections in our sample S3.…”
Section: The Luminosity Function Of a 1413supporting
confidence: 88%
“…Andreon 1998;Popesso et al 2006;Barkhouse, Yee, & López-Cruz 2007). This independence is likely a result of dynamical friction.…”
Section: The Bright End Of the Lfmentioning
confidence: 96%
“…It is a powerful observable to study the characteristics of galaxies and to compare environments of different densities (e.g., Trentham & Hodgkin 2002;Trentham, Sampson, & Banerji 2005;Tully et al 2002;Blanton et al 2003;Infante, Mieske, & Hilker 2003, and references therein). In particular, the faint end seems to be shaped by the environment (e.g., Popesso et al 2006;Barkhouse, Yee, & López-Cruz 2007), making deep spectroscopic study of dwarf galaxies and the comparison between those in field and clusters fundamental. The Schechter function (Schechter 1976) is commonly used to fit the LF of galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation of this observational result, however, is not straightforward since the different environmental processes can modify in a complex way both the number of objects and the luminosity of the perturbed galaxies. As a first indication we would be tempted to exclude for Virgo the combined effect of dwarf tidal disruption in the core of the cluster and galaxy harassment invoked by Popesso et al (2006), Barkhouse et al (2007), and de Filippis et al (2011) to explain the observed flattening in the core and the steepening in the periphery in the optical luminosity function of nearby clusters. We do not observe in Virgo any radial variations of the luminosity function either in the NUV or in the r-band (Rines & Geller 2008).…”
Section: Figmentioning
confidence: 99%